Applications of an unmanned aerial vehicle and thermal‐imaging camera to study ducks nesting over water. Issue 4 (25th October 2020) - Bushaw, Jacob D.; Ringelman, Kevin M.; Johnson, Michael K.; Rohrer, Trenton; Rohwer, Frank C.
Abstract: Finding and monitoring nests are key components of avian research, but they are often expensive, time‐consuming, and inefficient operations. This is certainly true for diving ducks that nest in wetlands with thick emergent vegetation where nests are typically located by teams of technicians that wade through a marsh and beat vegetation with sticks, hoping to flush incubating females or encounter nests without a female present. Taking advantage of recent advances in both unmanned aerial vehicles (UAVs) and thermal‐imaging cameras, our objectives were to (1) compare our ability to locate duck nests using a UAV and using traditional on‐foot searching methods, and (2) determine if nests monitored remotely with the UAV had different survival rates than nests monitored with traditional nest‐site visits. We searched for nests with a UAV system in southern Manitoba during the springs of 2018 and 2019. Using the UAV, we located 48 nests not found by ground crews, ground crews found 164 nests not found with the UAV, and 71 nests were found using both methods. Overall, nests were less likely to be detected with the UAV (0.34) than by ground crews (0.71), but surveys were completed approximately four times faster with the UAV. Detectability of nests varied among duck species (range = 0.55–0.04). We found no difference in nest survival between nests monitored with the UAV (0.95) and those repeatedly visited by ground crews (0.95). However, in 2018, ground monitoring resulted in 19 nests being abandoned by females, compared to only one monitored with the UAV. Our results demonstrate that UAVs equipped with thermal cameras can be used to find nests of ducks located over water, with greater success for species that nest earlier and those whose nests are not buried under matted vegetation. Furthermore, monitoring nests with the UAV resulted in lower rates of nest abandonment, and survival of nests monitored with the UAV was similar to that of nests monitored using traditional methods. Additional species‐ and habitat‐specific studies are needed to fully understand the utility and challenges associated with using UAVs equipped with thermal imaging to survey species of wetland wildlife. RESUMEN: Aplicaciones de vehículos aéreos no tripulado y cámaras térmicas para estudiar patos anidando sobre el agua Encontrar y monitorear nidos son componentes clave para el estudio de las aves, pero son normalmente operaciones ineficientes, costosas y que consumen mucho tiempo. Esto es especialmente cierto para los patos zambullidores que anidan en humedales con vegetación emergente densa, donde los nidos son encontrados por grupos de técnicos que caminan a través del humedal, golpeando la vegetación con palos esperando espantar hembras que están incubando o encontrar nidos sin la presencia de las hembras. Utilizando avances recientes en el desarrollo de vehículos aéreos no tripulados (UAV) y cámaras térmicas, nuestros objetivos fueron (1) comparar la capacidad de encontrar nidos utilizando UAV y utilizando métodos de búsqueda tradicionales y (2) determinar si los nidos monitoreados remotamente con UAV tienen tasas de supervivencia diferentes que los nidos monitoreados con visitas tradicionales al sitio de anidación. Buscamos nidos con un sistema UAV en el sur de Manitoba durante las primaveras de 2018 y 2019. Utilizando los UAV, encontramos 48 nidos que el equipo en campo no ubicó, el equipo en tierra localizó 164 nidos que no fueron localizados por el UAV y 71 nidos fueron encontrados utilizando ambas metodologías. En general, el UAV ubicó los nidos con menor probabilidad (0.34) que el equipos en tierra (0.71), pero los monitoreos fueron cuatro veces más rápidos utilizando el UAV. La detección de los nidos fue variable a través de las especies (rango = 0.55–0.04). No encontramos diferencias en la supervivencia de los nidos entre los nidos monitoreados por el UAV (0.95) y los que fueron repetidamente visitados por el equipo de tierra (0.95). Sin embargo, en 2018, 19 de los nidos monitoreados por el equipo de tierra fueron abandonados, mientras que solo uno fue abandonado utilizando el método de monitoreo con UAV. Nuestros resultados sugieren que UAV equipados con cámaras térmicas pueden ser utilizados para encontrar nidos de patos ubicados sobre el agua, con un éxito mayor en las especies que anidan temprano en la temporada y para aquellos nidos que no están enterrados en vegetación densa. Adicionalmente, el monitoreo de nidos con UAV resultó en una tasa menor de abandono y la supervivencia de los nidos monitoreados utilizando UAV fue similar a la supervivencia de los nidos monitoreados con métodos tradicionales. Necesitamos un mayor número de especies y estudios específicos a un hábitat para comprender enteramente la utilidad y los retos asociados por la utilización de UAV equipados con cámaras térmicas para monitorear especies silvestres en humedales.